Ubiquitin C-terminal hydrolase 1 is increased in migraine attack - Atescelik, M.; Yilmaz, M. (Elsevier Masson s.r.l., 2023)
Objective: This study aimed to determine the serum level of Ubiquitin C-terminal hydrolase 1 enzyme during a migraine attack and after its treatment. Methods: Blood samples of 43 patients and 30 healthy controls who presented to the emergency department with migraine attacks were analysed. Study sample was classified into three groups: Group 1 (patients presenting with migraine attack), Group 2 (4th hour after dexketoprofen treatment) and Group 3 (healthy control). Demographic data of patients, visual analogue scale and Ubiquitin C-terminal hydrolase 1 levels were analysed. Results: Median (IQR) Ubiquitin C-terminal hydrolase 1 levels were 13.70 (10.75–18.92) in Group 1, 9.45 (6.95–11.56) in Group 2 and 6.04 (3.88–8.72) ng/mL in Group 3; the Kruskal–Wallis test result showed a significant difference between the groups (P < 0.001). Following the Kruskal–Wallis test, the post-hoc Dunn test was performed for binary comparison between the groups, which revealed significant differences between all groups (Group 1–Group 2, Group 1–Group 3 and Group 2–Group 3 with P = 0.001, P < 0.001 and P = 0.008, respectively). Moreover, a significant positive correlation was found between VAS score and UCHL1 levels before treatment (r = 0.884, P < 0.001). Conclusion: UCHL1 levels of patients with migraine increase during acute attack and they can be used to assess the severity of attack and response to treatment. © 2022 Elsevier Masson SAS
Keywords: Migraine; Ubiquitin C-terminal hydrolase-1; UCHL1; VAS